PEREMPUAN DAN LITERASI MEDIA - Liliek Budiastuti Wiratmo (Pusat Studi Gender dan Anak (PSGA) IAIN Purwokerto, 2015)
The growth of media industry, both press and broadcasts (radio and television) increase the competition of media content toreach a large number of audiences through variety of rubric and broadcast programs. But this competetition doesn’t followed with a goodand save to consume content quality. Now on, female become the marketing frontline as well as product target that the media offer. To facethat condition, female need to have a good acknowledge about media industry so they can filter the offered informations